Legends, Inspirations and Space: Landscape Sacralization of the Sacred Site Mount Putuo - Pan, Yiwei (Religions, 2021)
Mount Putuo in Zhejiang Province, China, is the most important holy land of Guanyin in East Asia. Landscape sacralization is a key modality by which sacred meaning is constructed. This paper takes several examples—the Tidal Sound Cave ("chaoyin dong" 潮音洞), the Well of the Immortal Mei ("Meixian jing" 梅仙井), the Well of Ge Hong ("Ge Hong jing" 葛洪井), the Well of the Immortal ("xianren jing" 仙人井), and Duangu Pier ("Duan Gu daotou" 短姑道頭)—to analyze the three types of processes of sacralization. The Tidal Sound Cave is a re-construction of the founding myths; Well of the Immortal Mei, the Well of Ge Hong and the Well of the Immortal reflect harmony between local legends of Daoist immortals and the sacred Buddhist site; and the Duangu Pier accomplished its sanctification process in the course of local pilgrimage activities. By sorting out the mechanism and process of landscape sanctification and exploring the generation and renewal of landscape meaning, we can observe the logic of the construction of this sacred site.